2021
DOI: 10.1111/jpm.12727
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative emancipatory inquiry into relationships between people with mental disorders and health professionals

Abstract: Accessible summary What is known on the subject? A therapeutic alliance with people with mental disorders could help increase the efficacy of treatment. The paradigm shift from a paternalistic model to one that respects the person's autonomy has led to professionals accepting the active role of people with mental disorders making decisions that affect their treatment. What this paper adds to existing knowledge? People with mental disorders perceive paternalistic and stigmatizing attitudes from health pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…It appears to be of particular importance to men in their decisions to engage, disengage, and reengage with mental health services. As already suggested in existing literature, health professionals actively addressing safety and power dynamics earlier on in health management encounters could be a strategy to start discussing a healthy and trusting clinical environment in their interactions with male patients (Barrett et al, 2008; Beel et al, 2018; Chen et al, 2017; Martínez-Martínez et al, 2021; Seidler et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It appears to be of particular importance to men in their decisions to engage, disengage, and reengage with mental health services. As already suggested in existing literature, health professionals actively addressing safety and power dynamics earlier on in health management encounters could be a strategy to start discussing a healthy and trusting clinical environment in their interactions with male patients (Barrett et al, 2008; Beel et al, 2018; Chen et al, 2017; Martínez-Martínez et al, 2021; Seidler et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Martínez-Martínez et al [ 25 ] found that health professionals’ perceived negative attitudes were a significant concern to consumers and recommended increasing shared decision making and reflexive practice to improve the therapeutic alliance with consumers. Core to achieving this as part of ongoing engagement is the development of epistemic trust.…”
Section: Discussionmentioning
confidence: 99%
“…While not commonly listed with cognitive and clinical biases (Centre for Evidence-Based Medicine 2021; Croskerry 2015Croskerry , 2019, recognition continues to grow for this phenomenon as a type of bias within health care (Becker-Haimes et al 2021;Hinde et al 2021;Jamieson & Mason 2019). Knowledge of diagnostic overshadowing is particularly vital for nurses as they are not only hands-on care providers but lead advocates for patient care (Chuttoo & Chuttoo 2019;Mart ınez-Mart ınez et al 2021).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Knowledge of diagnostic overshadowing is particularly vital for nurses as they are not only hands‐on care providers but lead advocates for patient care (Chuttoo & Chuttoo 2019 ; Martínez‐Martínez et al . 2021 ).…”
Section: Introductionmentioning
confidence: 99%